Reactive Extrusion Printing for Simultaneous Crystallization‐Deposition of Metal–Organic Framework Films. Issue 15 (19th February 2022) - Al‐Ghazzawi, Fatimah; Conte, Luke; Richardson, Christopher; Wagner, Pawel
Abstract: Reactive extrusion printing (REP) is demonstrated as an approach to simultaneously crystallize and deposit films of the metal–organic framework (MOF) Cu3 btc2 (btc=1, 3, 5‐benzenetricarboxylate), also known as HKUST‐1. The technique co‐delivers inks of the copper(II) acetate and H3 btc starting materials directly on‐surface and on‐location for rapid nucleation into films at room temperature. The films were analyzed using PXRD, profilometry, SEM and thermal analysis techniques and confirmed high‐quality Cu3 btc2 films are produced in low‐dispersity interconnected nanoparticulate form. The porosity was examined using gas adsorption which showed REP gives Cu3 btc2 films with open interconnected pore structures, demonstrating the method bestows features that traditional synthesis does not. REP is a technique that opens the field to time‐efficient large‐scale fabrication of MOF interfaces and should find use in a wide variety of coating application settings. Abstract : Scalable fabrication methods for metal–organic framework (MOF) films are crucial for integrating this class of materials with applications. Reactive extrusion printing (REP) co‐delivers reactive inks that rapidly form micron‐thick interconnected nanoparticulate films of Cu3 btc2 (HKUST‐1) on‐demand and on‐location.